2009
DOI: 10.2341/08-95
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Ceramic Inlays Compared to Composite Restorations

Abstract: SUMMARYThis study compared the clinical performance of indirectly manufactured ceramic Evopress inlays with those of directly placed, fine particle hybrid Filtek Z250 composite restorations in posterior teeth.From January 2000 to October 2003, 109 patients received 264 Evopress (Wegold) ceramic inlays and 68 patients received 145 Filtek Z250 (3M ESPE) composite restorations in a dental office. Two-hundred and fifty ceramic inlays (95%) and 135 composite restorations (93%) were re-examined up to 57 months after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 21 publications
0
33
0
5
Order By: Relevance
“…Within the same time frame (12 y), we estimated a 10.5% failure probability for Empress CAD onlays and 9.5% for Empress CAD inlays. For a similar glass-ceramic (Evopress; Wegold, Wendelstein, Germany), 3 fractures were recorded from a total of 250 inlays after a mean period of 2.7 y (~0.5% annual failure rate) (Lange and Pfeiffer 2009). Conversely, the time that e.max CAD onlays are expected to show 10% of failure may take 30.3 y and inlays significantly longer, a difference revealed only when assuming an underlying failure distribution (Weibull).…”
Section: Discussionmentioning
confidence: 99%
“…Within the same time frame (12 y), we estimated a 10.5% failure probability for Empress CAD onlays and 9.5% for Empress CAD inlays. For a similar glass-ceramic (Evopress; Wegold, Wendelstein, Germany), 3 fractures were recorded from a total of 250 inlays after a mean period of 2.7 y (~0.5% annual failure rate) (Lange and Pfeiffer 2009). Conversely, the time that e.max CAD onlays are expected to show 10% of failure may take 30.3 y and inlays significantly longer, a difference revealed only when assuming an underlying failure distribution (Weibull).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the dimensional changes resulting from the polymerization are determined by the monomers of the polymer matrix, and the most common monomers are BisGMA, UDMA, UTMA, and Bis-EMA [13]. Nevertheless, the clinical performance of direct composites is still inferior to the performance of indirect ceramic restorations considering marginal adaptation, color match, and anatomic form [14]. A 3-year clinical study showed that indirect resin-based composite restorations have inferior esthetic and wear resistance compared to all-ceramic restorations [15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some studies showed statistically similar clinical outcomes to replacements for amalgams, bonded resin inlays, and bonded ceramic inlays in systematic reviews . One clinical study showed similar mean survival times between ceramic inlays and PCRS after 57 months.…”
mentioning
confidence: 99%